ختم النبوة في ضوء القرآن، في الآيات غير الصريحة (دراسة دلالية): The Seal of Prophet-hood in Light of the Qur’an: In the Non-Specific Verses (Semantic Study) - rahat khalil; Dr. Faryal Umbreen (Al-Amīr Research Journal for Islamic Studies, 2024)
The issue of the Seal of prophet hood holds a significant place in Islam, and the Qur’an has addressed it in great detail, as Allah says: “Muhammad is not the father of any of your men, but he is the Messenger of Allah and the Seal of the Prophets and Allah is All-Knowing of everything.” (33:40). Allah revealed this noble verse because, being the Knower of the unseen and the witnessed, He knew that false claimants of prophet hood would emerge. The Prophet (peace be upon him) also gave great attention to this belief and emphasized it in various ways, in both private and public settings. He left no doubt about it, leaving us with this belief clear and distinct. As the Messenger of Allah (peace be upon him) said: "There will be thirty liars in my Ummah, all of whom will claim to be prophets, and I am the Seal of the Prophets; there is no prophet after me." (Hadith) A reader of the Qur’an will find that there are explicit verses that directly indicate the Seal of prophet hood, while there are other verses that require reflection on their wording and structure to understand their implication for the Seal of prophet hood. This article focuses on analyzing the non-explicit verses, which contain subtle evidence for the Seal of prophet hood, highlighting the semantic nuances of these verses and explaining how the words and structures of these verses are organized, and the secrets they hold in their syntactical structure according to their various contexts. Therefore, the topic has been chosen under the title "The Seal of prophet hood in Light of the Qur’an, in the Non-Specific Verses: A Semantic Study." The importance of this study lies in its relation to the Qur’an and the sacred issue of the “Seal of Prophet Hood” The belief in the Seal of prophet hood is a unique characteristic of Prophet Muhammad (peace be upon him), and we firmly believe that our Prophet (peace be upon him) is the Seal of the Prophets and Messengers. Key words: Seal of prophet hood, Non-Specific Verses, Semantic Study